Healthy life-style: sociological approach - Dmitrievich, Panachev Valery; Ponomarev Nikolay Leonidovich, Kudryshov Evgeny Vasilevich, (Opción, 2019)
The analysis of the results of students’ health and healthy lifestyle problems study has been presented in the article. An experimental program of physical culture and technology of its realization was developed on the base of carried out research as a method. As a result, physical culture substantially assists in mental activity. It coincides with Aristotle’s affirmation about the fact that thoughts flow quicker when the body is warmed up by the walk. In conclusion, modern students aspire to support their health. Most tested students consider a healthy lifestyle as regular mills, good sleep, going in for sports and denial of unhealthy habits.